Artificial Intelligence for Knowledge Management First IFIP WG 12.6 International Workshop, AI4KM 2012, Montpellier, France, August 28, 2012, Revised Selected Papers - Mercier-Laurent, Eunika; Boulanger, Danielle (IFIP Advances in Information and Communication Technology, 2014)
This book features a selection of papers presented at the First IFIP WG 12.6 International Workshop on Artificial Intelligence for Knowledge Management, AI4KM 2012, held in Montpellier, France, in August 2012, in conjunction with the 20th European Conference on Artificial Intelligence, ECAI 2012. The 11 revised and extended papers were carefully reviewed and selected for inclusion in this volume. They present new research and innovative aspects in the field of knowledge management.